Chest pain–a common feature of ankylosing spondylitis. Issue 747 (January 1988) - Dawes, P. T.; Sheeran, T. P.; Hothersall, T. E.
Abstract : We compared the incidence, nature and frequency of chest pain in a group of 45 ankylosing spondylitis patients with an age and sex matched group of normals. Twenty-five ankylosing spondylitis patients had experienced recurrent chest pain compared to three normals, and had a significantly reduced chest expansion. The presence of chest pain in ankylosing spondylitis can be an early presenting feature of the disease (eight patients had chest pain before spinal symptoms), and is associated with more severe disease.